RIAU PROVINCE TOURISM WEBSITE IMPROVEMENT PROGRAM USING E-GOVQUAL AND IMPORTANCE PERFORMANCE ANALYSIS METHODS - Ichsan Ahmad Gunawan; Muhammad Jazman; Tengku Khairil Ahsyar; M. Afdal (Informatika, Universitas Jenderal Soedirman, 2023)
The Riau Province Tourism Office implements E-Government by building a website as a media public relations. This website is used to provide information on tourist destinations, facilities and news about Riau Province. Previously this website had never been evaluated so that the community's assessment of the quality of the Riau Province Tourism service site was unknown. For this reason, this study aims to analyze the service quality of the Riau Province Tourism Office website based on the perception or point of view of its users, in this case especially the people of Riau Province using the Electronic Government Quality (E-GovQual) and Importance Performance Analysis (IPA) methods. To assess the service quality of the Riau Province Tourism Office website using 6 dimensions and 28 E-GovQual attributes. The results of this study show that the total value of the performance score is Likert 3 (good) which is 3.30, the value of importance is 3.27, and the gap between performance and importance is 0.002 or > 0. The results of this study indicate that service performance has met the interests user. Thus the overall performance of the Riau Province Tourism Office website service is good and has fulfilled the interests of users. Furthermore, from the results of the IPA analysis, 7 attributes (EU1, TR1, FIE2, EU2, TR3, CS2, CAI3) are obtained with top priority and 5 attributes (EU3, FIE1, RB3, CA12, TR2) that need to be improved.